Development and Testing of a Patient Outcome Measure for Interprofessional Tuberculosis Care: A Delphi Study - Ardyansyah, Bau D.; Cordier, Reinie; Brewer, Margo; Parsons, Dave (Emerging Science Journal, 2025)
Background: A chronic medical condition such as tuberculosis can be physically and emotionally challenging for both health practitioners and patients and their families. Tuberculosis requires a team-based care model that provides resilience and coordinated work, such as the one offered by an interprofessional collaborative practice team. Despite the increasing interest in interprofessional-based care globally, there is a notable lack of measures to assess patient impact. We aimed to develop a patient outcome measure to quantify the functional impact of interprofessional care on tuberculosis patients. Methods: The study involved four phases: 1) developing a conceptual framework and creating items, 2) evaluating the construct through Delphi studies to obtain international consensus, 3) back-to-back translation into Indonesian, and 4) re-evaluating the construct with Delphi study to obtain Indonesian consensus. The consensus was reached if the Content Validity Index covers at least 70% agreement from experts, an interquartile range <1, and a median score of 4 or 5 on a 5-point Likert-type scale. The COnsensus-based Standards for the Selection of Health Measurement INstruments (COSMIN) guidelines were used to assess item relevance, comprehensibility, and comprehensiveness. Results: A total of 65 international and 61 Indonesian participants in the Delphi studies. The final instrument consists of 44 items organized into five domains. All items were relevant to the construct being measured and deemed understandable, and significant concerns related to TB care were comprehensively addressed in the instrument. Conclusion:The findings indicate that the instrument content validity was good, fulfilling COSMIN requirements for items' relevance, comprehensibility, and comprehensiveness. Doi: 10.28991/ESJ-2025-09-01-08 Full Text: PDF